The impact of p53 on aristolochic acid I-induced nephrotoxicity and DNA damage in vivo and in vitro - Sborchia, Mateja; De Prez, Eric G; Antoine, Marie-Hélène; Bienfait, Lucie; Indra, Radek; Valbuena, Gabriel; Phillips, David H; Nortier, Joëlle L; Stiborová, Marie; Keun, Hector C; Arlt, Volker M (Archives of toxicology, 2019)
Exposure to aristolochic acid (AA) is associated with human nephropathy and urothelial cancer. The tumour suppressor TP53 is a critical gene in carcinogenesis and frequently mutated in AA-induced urothelial tumours. We investigated the impact of p53 on AAI-induced nephrotoxicity and DNA damage in vivo by treating Trp53(+/+), Trp53(+/-) and Trp53(-/-) mice with 3.5 mg/kg body weight (bw) AAI daily for 2 or 6 days. Renal histopathology showed a gradient of intensity in proximal tubular injury from Trp53(+/+) to Trp53(-/-) mice, especially after 6 days. The observed renal injury was supported by nuclear magnetic resonance (NMR)-based metabonomic measurements, where a consistent Trp53 genotype-dependent trend was observed for urinary metabolites that indicate aminoaciduria (i.e. alanine), lactic aciduria (i.e. lactate) and glycosuria (i.e. glucose). However, Trp53 genotype had no impact on AAI-DNA adduct levels, as measured by 32P-postlabelling, in either target (kidney and bladder) or non-target (liver) tissues, indicating that the underlying mechanisms of p53-related AAI-induced nephrotoxicity cannot be explained by differences in AAI genotoxicity. Performing gas chromatography-mass spectrometry (GC-MS) on kidney tissues showed metabolic pathways affected by AAI treatment, but again Trp53 status did not clearly impact on such metabolic profiles. We also cultured primary mouse embryonic fibroblasts (MEFs) derived from Trp53(+/+), Trp53(+/-) and Trp53(-/-) mice and exposed them to AAI in vitro (50 µM for up to 48 h). We found that Trp53 genotype impacted on the expression of NAD(P)H:quinone oxidoreductase (Nqo1), a key enzyme involved in AAI bioactivation. Nqo1 induction was highest in Trp53(+/+) MEFs and lowest in Trp53(-/-) MEFs; and it correlated with AAI-DNA adduct formation, with lowest adduct levels being observed in AAI-exposed Trp53(-/-) MEFs. Overall, our results clearly demonstrate that p53 status impacts on AAI-induced renal injury, but the underlying mechanism(s) involved remain to be further explored. Despite the impact of p53 on AAI bioactivation and DNA damage in vitro, such effects were not observed in vivo.
Keywords: exprese genu; Gene Expression; poškození DNA; Kidney Tubules, Proximal; Male; fibroblasty; DNA adducts; Mice, Knockout; DNA Damage; Fibroblasts; Cytochrome P-450 CYP1A1; proximální tubuly ledvin; cytochrom P-450 CYP1A1; mužské pohlaví; nádorový supresorový protein p53; Mutagens; Aristolochic Acids; Kidney Function Tests; myši knockoutované; kultivované buňky; kyseliny aristolochové; mutageny; NAD(P)H dehydrogenasa (chinon); Animals; Mouse embryonic fibroblasts; zvířata; Aristolochic acid I; myši inbrední C57BL; vyšetření funkce ledvin; Mice, Inbred C57BL; Cells, Cultured; Tumour suppressor p53; Carcinogen metabolism; Mouse models; NAD(P)H Dehydrogenase (Quinone); Tumor Suppressor Protein p53